Modificações vocais produzidas pelo finger kazoo - Christmann, Mara Keli (2012)
Vocal exercises semioccluded vocal tract (SOVT) of include finger kazoo (FK). Objectives: to correlate vocal-acoustic and auditory perception modifications of the glottal source, spectrograph acoustic vocal modifications and self-evaluation after FK. Methods: A cross-sectional analytic quantitative observation study. The 46 adult women age between 18 and 40 without vocal complaints and laryngeal alterations, emitted the vowel /a:/ before (M1); immediately after three series of 15 FK repetitions (30 seconds rest) (M2); and five minutes after (M3); vocal self-evaluation in M2 and M3. Vocal analyses by means of the RASATI scale, programs Multi Dimension Voice Program Advanced and Real Time Spectrogram (Kay Pentax®). The spectrographs and the RASATI results were evaluated by judges. Kappa, Friedman, Wilcoxon and Chi-square tests. Results: Increase of fundamental frequency (f0); reduction of amplitude variation (vAm); and degree of sub-harmonics (DSH) in M2. No difference in the RASATI. Significant positive correlations: standard deviation of the f0 (STD) with breathiness and asthenia; measures of jitter, frequency variation (vf0) and soft phonation index (SPI) with hoarseness, breathiness, asthenia, and instability; measures of shimmer and vAm with hoarseness and breathiness; vAm with asthenia; degree and number of unvoiced segments (NUV and DUV) with breathiness; STD, jita, SPI, smoothed pitch perturbation quotient (sPPQ), smoothed amplitude perturbation quotient (sAPQ), vf0 and vAm with instability. Significant negative correlations: voice turbulence index (VTI) with asthenia; jitter and SPI measures with tension; f0 higher (fhi), f0 lower (flo) and f0 with hoarseness and breathiness; instability with flo. Wideband: improvement of F2, F3, F4 intensity and of high frequencies (hf), F2, F3 definition and trace regularity (M1XM2); F and hf intensity, and F3, F4 definition, increase in hf noise (M1XM3), worsening in the trace regularity (M2XM3). No alteration (NA) in F bandwidth, F1 definition, low, medium and hf noise (M1XM2XM3), and medium and low frequencies M1XM3). Narrowband: improvement in hf intensity, harmonics definitions and trace regularity, NA in noise between low harmonics and hf (M1XM2); improvement of hf intensity, in all vocal spectrogram and trace regularity, worsening in noise between harmonics, NA in low and hf noise, harmonics substitution for noise in all vocal spectrogram and low, medium and hf (M1XM3); NA in the presence of subharmonics (M1XM2XM3). Improvement in voice reference. Positive correlation between better voice and F3 intensity (wideband M1XM3), and harmonics substitution for noise in medium frequencies, definition and harmonics number (narrowband - M1XM3). Conclusion: FK generated noise reduction, increase of f0, vocal stability and harmonic energy. In general, hoarseness, asthenia, breathiness and instability positively correlated with jitter, shimmer, STD, SPI, vf0, vAm, NUV, DUV measures and negatively with frequency and VTI measures. The tension negatively correlated with jitter and SPI measures. There was an increase in hf intensity, F intensity and definition, trace regularity and harmonics definition. Better voice, according to F3 intensity, definition and number of harmonics and harmonics substitution for noise in medium frequencies. Keywords: Voice. Phonation. Rehabilitation. Speech Acoustics